Systematic Literature Review: Cooperative Learning Model in Physical Education Learning in Elementary Schools - Berabo, Ranti Humayrah; Rahmat, Alit; Carsiwan, Carsiwan; Nugraha, Reshandi (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to determine and describe the influence of the Cooperative Learning model on physical education learning in elementary schools. The method used was a Systematic Literature Review, where the search results found 177 journals from 2014 to 2023 which were selected in stages and systematically and also selected from 2 types of cooperative learning models, namely Cooperative Learning Type Student Teams Achievement Division (STAD and Cooperative Learning Jigsaw Type. The research results show that the Cooperative Learning model in physical learning in elementary schools has a positive influence on students. The two studies state that Cooperative Learning can improve learning outcomes for students.